Population Development in the Ústí Region (Main Trends and Demographic Ageing) - Kaćirek, Petr (Procesy rozwojowe ludności w regionie Usti (główne trendy i problem demograficznego starzenia się), 2008)
The article presented selected problems of population development in the Ústí region. Discussed demographic ageing as the most interesting topic in the population development of the majority of demographically developed countries. Ageing at the top of the age pyramid is caused by prolonging human life and that leads to increasing live expectancy to see the rise of percentage of old and very old people in the population. Ageing on the base of the age pyramid is caused by decreasing number of born that leads to reduction of the children in the population. (MP)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 247-256